2018
DOI: 10.1177/0269215518804018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of theta-burst stimulation on unilateral spatial neglect following stroke: a systematic review

Abstract: Objective: To evaluate the effectiveness of theta-burst stimulation for the treatment of stroke-induced unilateral spatial neglect. Data sources: A systematic literature search was conducted from the inception of each database to 30 June 2018 using CINAHL, EMBASE, PubMed, PsycINFO, and Scopus. Review methods: Articles were included if theta-burst stimulation was used to treat neglect following a stroke. The additional a priori inclusion criteria were as follows: (1) ⩾3 adult (⩾18 years) participants, (2) ⩾50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(166 reference statements)
0
10
0
Order By: Relevance
“… 134 Repetitive transcranial magnetic stimulation in the posterior parietal cortex, and theta-burst stimulation, improved USN after stroke. 135 Very low-quality evidence suggested that tDCS has a beneficial effect in improving USN after stroke. 136 …”
Section: Unilateral Spatial Neglectmentioning
confidence: 99%
“… 134 Repetitive transcranial magnetic stimulation in the posterior parietal cortex, and theta-burst stimulation, improved USN after stroke. 135 Very low-quality evidence suggested that tDCS has a beneficial effect in improving USN after stroke. 136 …”
Section: Unilateral Spatial Neglectmentioning
confidence: 99%
“…There are a number of NIBS studies on the cerebellar hemisphere; however, studies of cerebellar vermis are relatively rare. Intermittent theta burst stimulation (iTBS), a type of repetitive transcranial magnetic stimulation (rTMS), which serves as a NIBS method, has been proved to have the positive effects on neuroplasticity and central nervous system excitability ( Cotoi et al, 2019 ; Katagiri et al, 2020 ). It exhibits long lasting effects compared with traditional TMS with shorter stimulation period than traditional TMS ( Kim et al, 2015 ; Hurtado-Puerto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors found mild evidence of the efficacy of rTMS for the treatment of neglect, no significant positive effect was found regarding tDCS. Furthermore, recently one systematic review on TBS and neglect (111) found a positive effect on the symptoms although a strong heterogeneity of protocols and assessment was found. As stated, only cerebrovascular disease patients were included; the results were biased by the small number of patients and strong heterogeneity of the protocol of NIBS.…”
Section: Discussionmentioning
confidence: 99%